Role Of Families With Hospitalization Anxiety Levels In Children - Nurlina; Ilhamsyah; Ayu Astuti Suardi (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2019)
Based on data from the WHO (World Health Organization) in 2012 about 52% of patients treated in the hospital where children with various illnesses. Data on the national hospital collection in the United States is estimated that more than 5 million children are hospitalized due to surgical procedures and more than 50% of these experience anxiety and stress. This study aims to determine the relationship of the role of the family with the level of anxiety hospitalization in children in the rose care room of H. Andi Sulthan Daeng Radja Bulukumba Hospital in 2019. This study uses a cross-sectional design type. The sample in this study as many as 47 people with simple random sampling technique research methods using questionnaires. Data were processed univariately and bivariate and analyzed using the Kolmogorov Smirnov alternative chi-square test. The results showed that the good role of the family towards hospitalization of the majority of good children was 30 (63.8%), while the majority of children's anxiety levels were categorized as mild anxiety as much as 23 respondents (48.9%). The test used in the Kolmogorov Smirnov alternative chi-square test was obtained p-value = 0.001> 0.005 so it can be concluded that there is a relationship between the role of family and the level of anxiety of hospitalization in children in the rose care room of H. Andi Sulthan Daeng Radja Bulukumba 2019 Hospital.